Composite Materials Science and Engineering - Chawla, Krishan K. (Springer International Publishing : Imprint: Springer, 2019)
The fourth edition of Krishan Chawla's widely used textbook, Composite Materials, offers integrated and completely up-to-date coverage of composite materials. The book focuses on the triad of processing, structure, and properties, while providing a well-balanced treatment of the materials science and mechanics of composites. In this edition of Composite Materials, revised and updated throughout, increasing use of composites in industry (especially aerospace and energy) and new developments in the field are highlighted. New material on the advances in non-conventional composites (which covers polymer, metal and ceramic matrix nanocomposites), self-healing composites, self-reinforced composites, biocomposites and laminates made of metals and polymer matrix composites is included. Examples of practical applications in various fields are provided throughout the book, with extensive references to the literature. The book is intended for use in graduate and upper-division undergraduate courses and as a reference for the practicing engineers and researchers in industry and academia. Updated and enlarged fourth edition of a widely used text; Offers integrated and completely up-to-date coverage of composite materials; Includes many new exercises and illustrations, new material on advances in polymer matrix composites, metal matrix composites and ceramic matrix composites; Emphasizes new applications in aerospace and energy materials. A new chapter on Recovery and Recycling has been added. Cover illustration A cutout of LEAP jet engine. The arrow on the right hand side of the figure points to the high pressure turbine part where shrouds made of ceramic matrix composites (SiC fiber/SiC matrix) are used. The blades in the front section are made of carbon fiber reinforced epoxy composite. (Courtesy of General Electric Co.).